Evaluasi Hasil Persilangan Ayam Lurik, Ayam Merawang dan Ayam Komering 267 Evaluasi Hasil Persilangan Ayam Lurik, Ayam Merawang dan Ayam Komering - Depison, Depison (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2006)
This research was aimed to study the breeding result between Lurik chicken versus Merawang  and  Komering  chicken  and  between  Merawang and  Komering  chicken..  Experimental  variables  were  taken  in  this  research were  egg  production,  egg  weight, fertility, hatched weight, daily weight gain, feed efficiency, chicken feather colour, comb shape, leg colour, skin and meat colour. Evaluated data was observed from the breeding of Lurik, Merawang and  Komering chickens, progeny of Lurik versus Merawang, progeny of Lurik versus Komering and progeny of Komering versus Merawang. Observed data was analysed by addition, persentage and deviasi standard (X ± sd) (Steel dan Torrie, 1993). T test  was  used  to  compare  egg  production,    egg  weight,  fertility,  hatched  weight,  daily weight gainand  feed efficiency  among the breeding treatments using  Siegel instruction (1994). Based on the research, it could be concluded : 1) egg weight and hatched weight of merawang were  better than Lurik, Komering, progeny of Lurik versus Merawang, Lurik versus Komering  and Merawang versus Komering, 2) The Productivity of breed of Lurik versus Merawang was higher than the breed of Lurik versus Komering and Merawang versus Komering. 3)  The breed of Komering versus Lurik was not signifivantly different in  increasing  of  egg  production  and  decreasing  of  feed  conversion.  4)    There  was  no difference of feed comsumption between Merawang, Komering and progenys of Merawang and Komering versus Lurik.